Child Labor and Rainfall Deviation: Panel Data Evidence from Rural Vietnam. (10th October 2019) - Trinh, Trong‐Anh; Posso, Alberto; Feeny, Simon
Abstract : Rainfall shocks to the agricultural sector can pull children into agricultural work and/or household chores. This is problematic because both forms of child work are potentially precarious. This study examines the relationship between rainfall deviations and child labor for rural households in Vietnam using panel data covering the period 2006–14. We classify child labor into agricultural and nonagricultural activities as well as household chores. We study children's entrance into work and the time intensity of work. Using child‐level fixed effects, we find evidence that above‐average rainfall is associated with children entering agricultural work as well as being pulled into (and spending more time doing) household chores. Our findings suggest that intra‐household experiences of exogenous weather shocks are likely to vary at the individual level, suggesting a need for a more tailored approach to policymaking.